1996
DOI: 10.1002/(sici)1097-0177(199603)205:3<319::aid-aja11>3.0.co;2-#
|View full text |Cite
|
Sign up to set email alerts
|

Localization of cytosolic aldehyde dehydrogenase in the developing chick retina: In situ hybridization and immunohistochemical analyses

Abstract: Cytosolic aldehyde dehydrogenase (ALDH) mRNA is present at high levels in the undifferentiated chick retina. Tissue maturation is accompanied by a 20–25× decrease in transcript levels. To determine the spatial and temporal distribution pattern of the ALDH transcript and its encoded protein in the developing retina, in situ hybridization and immunohistochemical analyses were carried out using chick embryos at different stages of development. The ALDH transcript and protein were detected at the earliest stage te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 38 publications
(29 reference statements)
1
14
0
Order By: Relevance
“…As in the mouse retina, the dorsal retinal enzyme in chick has been identified as a class-1 aldehyde dehydrogenase (Godbout et al, 1996). Because we had observed that an antiserum raised against class-1 aldehyde dehydrogenase of the rat (Lindahl et al, 1983) cross-reacts with the corresponding chick enzyme, we probed retina sectors, as sketched in Figure 1, by immunoblotting.…”
Section: Distribution Of Class-1 Aldehyde Dehydrogenase Immunoreactivitymentioning
confidence: 99%
“…As in the mouse retina, the dorsal retinal enzyme in chick has been identified as a class-1 aldehyde dehydrogenase (Godbout et al, 1996). Because we had observed that an antiserum raised against class-1 aldehyde dehydrogenase of the rat (Lindahl et al, 1983) cross-reacts with the corresponding chick enzyme, we probed retina sectors, as sketched in Figure 1, by immunoblotting.…”
Section: Distribution Of Class-1 Aldehyde Dehydrogenase Immunoreactivitymentioning
confidence: 99%
“…RA can be detected in both the dorsal and ventral regions of the eye (Marsh-Armstrong et al 1994;McCaffery et al 1992) and the relative amounts change with developmental age (McCaffery et al 1993;Mey et al 1997). The RA-synthesising enzyme Raldh1 is expressed in the dorsal retina (McCaffery et al 1991;McCaffery et al 1992;Godbout et al, 1996), Raldh3 is expressed in the ventral retina (McCaffery et al 1999;Grun et al 2000;Mic et al 2000;Suzuki et al 2000) and Raldh2 is expressed in the optic vesicle (Haselbeck et al 1999), at the ventral edge of the eye field (McCaffery et al 1999) and in the periocular mesenchyme (Niederreither et al 1997;Blentic et al, 2003). Cyp26A1 is expressed in an equatorial region of the mouse eye between the dorsal Raldh1 and ventral Raldh3 synthetic domains (Fujii et al 1997;de Roos et al 1999;McCaffery et al 1999;Wagner et al 2000), a function fulfilled by Cyp26B1 and C1 in the chick embryo (Reijntjes et al 2003;Reijntjes et al 2004) thus creating a RA free region and dividing the eye into three zones.…”
Section: Introductionmentioning
confidence: 99%
“…As a control for ALDH-I expression we also examined sections of E9.5 whole-mount stained embryos, and observed strong expression in the dorsal retina ( Fig. 2C), a site previously shown to have abundant expression of this enzyme in both mouse embryos McCaffery et al, 1991) and chick embryos (Godbout et al, 1996). Sections of E7.5 embryos stained for RARa mRNA indicated expression in all tissues; i.e., embryonic ectoderm, mesoderm, and endoderm, as well as extraembryonic ectoderm, mesoderm, and endoderm, including the allantois and amnion (Fig.…”
Section: Detection Of Mrnas For Adh-iv Aldh-i and Rars At Stage E75mentioning
confidence: 66%
“…However, prior to this study there was no evidence for expression of any form of ALDH that can convert retinal to RA at this stage of embryogenesis. ALDH-I had previously been found to function as a retinal dehydrogenase (Lee et al, 1991;El Akawi and Napoli, 1994;Bhat et al, 1995), and its expression had been observed in the dorsal retina of E9.5 mouse embryos (McCaffery et al, 1991) and stage 14 chick embryos (Godbout et al, 1996), suggesting that it might participate in RA synthesis in the developing retina (McCaffery et al, 1992). Our findings now indicate that ALDH-I is expressed in primitive streak mesoderm at E7.5 and may thus play an earlier role in RA synthesis than first suspected.…”
Section: Discussionmentioning
confidence: 99%